Cytotoxic Activity Screening of Fungal Extracts Derived from the West Sumatran Marine Sponge Haliclona fascigera to Several Human Cell Lines: Hela, WiDr, T47D and Vero - Dian Handayani, Wildan Rasyid, Rustini, Elmi Nurhaidah Zainudin, Triana Hertiani (Journal of Applied Pharmaceutical Science, 2018)
Cytotoxic activity of twenty extracts of fungal derived from marine sponge Haliclona fascigera collected from West Sumatera was evaluated by using Brine Shrimps Lethality Test (BSLT) and MTT assay on Hela, WiDr, T47D and Vero cells. In BSLT result, all fungal extracts were cytotoxic because their LC50 < 1000 ppm, and ranging from 1 to 335 ppm. While sixteen extracts (80%) were toxic (LC50 < 100 ppm) and further tested its cytotoxic activity against HeLa, Widr, T47D and Vero cell lines. A single 100 μg/mL dose of each extract was employed with 72 h of incubation for all tests. Doxorubicin was used as the positive control. The fungal extract of WR6 showed the highest MTT cytotoxicity with IC50 values of 47.4, 67.1, 118.3 and 163.37 ppm against WiDr, T47D, HeLa and Vero cell lines respectively. Therefore, this extract was chosen to be a good candidate for further studies as a new anticancer drug in the treatment of human cancer.
Keywords: Cytotoxic activity, Haliclonafascigera, marine derivedfungi, Brine Shrimp LethalityTest (BSLT), MTT assay.